Concepciones de la historia y el pasado durante la Revolución Inglesa. El caso de Thomas May - Kwiatkowski, Nicolás (Cuadernos de Historia Moderna, 2009)
This paper analyzes Thomas May’s main historiographic convictions, as well as the several conceptions of historical time present in his works. To that end, it explores his life and literary productions, focusing specially on his historical writings, but also taking into account some of his plays and translations. It also attempts a comparison between May’s views and those of a contemporary historian that also wrote a History of the English Revolution, the much more famous Edward Hyde, Earl of Clarendon.